1995
DOI: 10.1002/j.1460-2075.1995.tb07273.x
|View full text |Cite
|
Sign up to set email alerts
|

VAMP-2 and cellubrevin are expressed in pancreatic beta-cells and are essential for Ca(2+)-but not for GTP gamma S-induced insulin secretion.

Abstract: VAMP proteins are important components of the machinery controlling docking and/or fusion of secretory vesicles with their target membrane. We investigated the expression of VAMP proteins in pancreatic beta‐cells and their implication in the exocytosis of insulin. cDNA cloning revealed that VAMP‐2 and cellubrevin, but not VAMP‐1, are expressed in rat pancreatic islets and that their sequence is identical to that isolated from rat brain. Pancreatic beta‐cells contain secretory granules that store and secrete in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
170
1
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(183 citation statements)
references
References 59 publications
11
170
1
1
Order By: Relevance
“…Direct analysis of membrane capacitance has directly shown that GppNHp induces exocytosis [36] and it is likely that the same final steps in the exocytotic pathway are activated by Ca 2+ or by GppNHp. Previous work on insulin-secreting cells had shown that secretion induced by GTPTS was insensitive to tetanus and botulinum B neurotoxins despite extensive cleavage of VAMP, and inhibition of Ca2+-induced secretion, leading to the suggestion that VAMP is essential for the CaZ+-induced secretion but not that induced by non-hydrolysable GTP analogues [29]. The present data from chromaffin cells show, in contrast, that both stimuli are neurotoxin D-sensitive and therefore act via a VAMPdependent pathway.…”
Section: Resultssupporting
confidence: 40%
See 2 more Smart Citations
“…Direct analysis of membrane capacitance has directly shown that GppNHp induces exocytosis [36] and it is likely that the same final steps in the exocytotic pathway are activated by Ca 2+ or by GppNHp. Previous work on insulin-secreting cells had shown that secretion induced by GTPTS was insensitive to tetanus and botulinum B neurotoxins despite extensive cleavage of VAMP, and inhibition of Ca2+-induced secretion, leading to the suggestion that VAMP is essential for the CaZ+-induced secretion but not that induced by non-hydrolysable GTP analogues [29]. The present data from chromaffin cells show, in contrast, that both stimuli are neurotoxin D-sensitive and therefore act via a VAMPdependent pathway.…”
Section: Resultssupporting
confidence: 40%
“…We have shown here that recombinant His6-tagged botulinum neurotoxin D light chain cleaves VAMP but not syntaxin or SNAP-25 in permeabilised chromaffin cells and substantially inhibits both Ca2+-induced and GppNHp-induced catecholamine release suggesting that one or more VAMPs are essential in both cases. This differs from the situation in insulin-secreting cells where it has been suggested that VAMPs are not required for GTPTS-induced secretion [29]. While botulinum neurotoxin E is believed to be specific for SNAP-25, neurotoxin C1 has recently been shown to cleave both syntaxin and SNAP-25 in chromaffin cells [46].…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…4B, lanes 2 and 4). Synaptotagmin III is localized in the insulin granules (19), whereas VAMP-2 exists in both granules and SLMVs in beta cells (31). These results indicate an association of granuphilin-a with insulin-containing dense-core granules in beta cells.…”
Section: Molecular Cloning Of a Novel Rabphilin-3-likementioning
confidence: 89%
“…4A, upper panel), whereas synaptophysin was enriched at fractions 6 and 7 (lower panel). Synaptophysin, an integral membrane protein of SSVs in neurons, is absent in the insulin granules, but present in the SLMVs in beta cells (12,19,31). Thus, the two types of secretory vesicles were clearly separated.…”
Section: Molecular Cloning Of a Novel Rabphilin-3-likementioning
confidence: 94%